Classroom Instruction. (October 2014) - McNaughton, Stuart
Abstract Marie Clay's body of work has influenced classroom instruction in direct and indirect ways, through large overarching themes in our pedagogical content knowledge as well as specific smart practices. This paper focuses on her the contributions to our thinking about instruction which come from two broad theoretical concepts; emergent literacy and tutorial for teaching. These have contributed to shifts in the ways we think about instruction and provide a basis for the development and retuning of instructional practices.